2018
DOI: 10.1103/physrevb.98.075301
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced specular Andreev reflection in bilayer graphene

Abstract: Andreev reflection in graphene is special since it can be of two types, retro or specular. Specular Andreev reflection (SAR) dominates when the position of the Fermi energy in graphene is comparable to or smaller than the superconducting gap. Bilayer graphene (BLG) is an ideal candidate to observe the crossover from retro to specular since the Fermi energy broadening near the Dirac point is much weaker compared to monolayer graphene. Recently, the observation of signatures of SAR in BLG have been reported expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…However, it has been demonstrated that in monolayer graphene, where low energy electrons behave as massless Dirac fermions in a gapless band structure, 2 the energy dispersion is such that, for low Fermi levels, the hole component of the wave function travels back in the normal region in a trajectory that is parallel to that of the reflected electron, thus undergoing a specular Andreev reflection. This effect has been predicted by Beenakker in 2006 3 in a model for monolayer graphene, which was further extended to bilayer graphene, 4,5 and experimentally observed only very recently [5][6][7][8] Further suggestions have been made for experimental observation of Andreev scattering using N/SC interfaces based on different materials, such as transition metal dichalcogenides 9,10 and their heterostructures, 11 as well as on borophene. 12 A NS interface in monolayer black phosphorus 13 has also been recently theoretically proposed as a venue for the observation of Andreev reflection.…”
Section: Introductionmentioning
confidence: 57%
“…However, it has been demonstrated that in monolayer graphene, where low energy electrons behave as massless Dirac fermions in a gapless band structure, 2 the energy dispersion is such that, for low Fermi levels, the hole component of the wave function travels back in the normal region in a trajectory that is parallel to that of the reflected electron, thus undergoing a specular Andreev reflection. This effect has been predicted by Beenakker in 2006 3 in a model for monolayer graphene, which was further extended to bilayer graphene, 4,5 and experimentally observed only very recently [5][6][7][8] Further suggestions have been made for experimental observation of Andreev scattering using N/SC interfaces based on different materials, such as transition metal dichalcogenides 9,10 and their heterostructures, 11 as well as on borophene. 12 A NS interface in monolayer black phosphorus 13 has also been recently theoretically proposed as a venue for the observation of Andreev reflection.…”
Section: Introductionmentioning
confidence: 57%
“…In SAR process, an incident electron will be specularly reflected as the hole. Up to now, the SAR is discovered and studied extensively in the monolayer graphene [10][11][12][13][14][15][16][17] , bilayer graphene [18][19][20] , topological insulator 21 , Weyl semimetal [22][23][24] , nodal-line semimetal 25 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…3 We next explore the effect of parallel magnetic field as it is predicted that Zeeman splitting of graphene's Dirac cones will lead to the observation of specular Andreev processes at zero DC bias. 4 Figure 2A shows a schematic energy vs momentum diagram of the NbN/g interface under an in-plane magnetic field. Zeeman splitting breaks the spin degeneracy, energetically separating the graphene bands into two copies with opposite spins (see Figure S5 for details).…”
mentioning
confidence: 99%
“…The probability of this process strongly depends on the band structure of the normal metal and the properties of the interface. Graphene, because of its Dirac band structure with a highly tunable Fermi level, is an enticing avenue to explore the role of the normal metal’s electronic properties on Andreev processes. Initial experiments by Efetov in 2016 demonstrated the effect of graphene’s Dirac electronic structure on Andreev processes, identifying intraband Andreev processes (RAR) and interband Andreev processes (SAR). Under the application of perpendicular magnetic fields, graphene hosts chiral QH edge states, which has allowed for the investigation of Andreev process from integer QH states, which manifest non-Abelian zero modes of Majorana Fermions. , However, there are still many unanswered questions such as how junction transparency and the proximity effect in graphene evolve under large perpendicular magnetic fields in the integer and fractional QH regime and the role of interfacial vortices on the junction properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation